Exploring the impact of entrepreneurial challenges on student motivation at the Innobiz DUT centre for entrepreneurship and innovation - Chitamba, Anos; Mugano, Gift; Mbona, Sizwe; Chitamba, Norman (Edelweiss Applied Science and Technology, 2025)
This study examines the impact of entrepreneurial challenges on student motivation at the Innobiz Centre for Entrepreneurship and Innovation at Durban University of Technology (DUT). Based on the Theory of Planned Behavior, the research analyzes how financial, psychological, experiential, and time-related obstacles influence students’ attitudes, perceived behavioral control, and subjective norms, ultimately affecting their entrepreneurial intentions. A quantitative methodology was employed, collecting data from 76 student entrepreneurs through structured questionnaires, which were analyzed using descriptive and inferential statistics, including Spearman’s rho correlations. The findings indicate that while intrinsic motivators—such as autonomy, passion, and the excitement of entrepreneurship—have a strong positive effect on motivation, external challenges significantly influence perceived behavioral control and entrepreneurial self-efficacy. The lack of institutional and community support exacerbates cultural stigma and restricts collaboration, while financial and academic limitations appear to operate independently of peer networks. This study highlights the essential role of incubator support structures in enhancing entrepreneurial resilience and suggests the need for targeted interventions to address systemic barriers, promote interdisciplinary engagement, and cultivate intrinsic motivation. These insights are valuable for designing more inclusive and effective entrepreneurial ecosystems within higher education.